2013
DOI: 10.1111/socf.12002
|View full text |Cite
|
Sign up to set email alerts
|

Race and Reciprocity: Inter‐household Exchanges in a Multiracial Neighborhood

Abstract: This study investigates the degree to which African-American households are socially integrated into a multiracial, middle-class suburban neighborhood near Dallas, Texas. Although U.S. neighborhoods are becoming increasingly heterogeneous in composition, little is known about black households' participation in social and informational networks within multiracial middle-class neighborhoods. Drawing on theories of the gift and social capital, we view neighborhoods in terms of complex patterns of interhousehold e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In part, homogenous networks are maintained by homophily, or individual preferences for forming relationships with others who appear similar to oneself (see Blau ; Marsden ). Yet segregation likewise occurs when individuals lack the opportunity to build networks comprised of diverse others—a matter of propinquity (Blau ; Damaske ; Homans ; Ignatow et al ). At the macro level, workers lack exposure to racial/ethnic outsiders as a result of residential segregation and migration patterns (see Mouw ; Wilson ) .…”
Section: Teams and Contactmentioning
confidence: 99%
“…In part, homogenous networks are maintained by homophily, or individual preferences for forming relationships with others who appear similar to oneself (see Blau ; Marsden ). Yet segregation likewise occurs when individuals lack the opportunity to build networks comprised of diverse others—a matter of propinquity (Blau ; Damaske ; Homans ; Ignatow et al ). At the macro level, workers lack exposure to racial/ethnic outsiders as a result of residential segregation and migration patterns (see Mouw ; Wilson ) .…”
Section: Teams and Contactmentioning
confidence: 99%
“…Research before the pandemic showed that interaction with non-residential family members and friends enhanced older adults’ mental well-being ( Becker et al, 2019 ). Inter-household contact often took the form of face-to-face meetings and activities, supplemented by virtual interactions via telephone or video calls, text messaging, and social media ( Ignatow et al, 2013 ; Sandstrom and Dunn, 2014 ; Lomanowska and Guitton, 2016 ). When regular in-person contact was not viable, such as for transnational families and in disaster scenarios, individuals often resorted to virtual communication to maintain long-distance relationships with family members and friends, along with occasional in-person visits ( Madianou and Miller, 2013 ; Hu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, I argue that the manifestation of these theoretical frameworks differs according to the respondents' race or ethnicity and the race or ethnicity of the neighbors or neighborhood they are assessing (see also Ignatow et al. ). Whether respondents use pure‐race or racial proxy explanations for their neighborhood preferences depended largely on that person's social location and the racial or ethnic composition of the neighborhood they were considering.…”
Section: Discussionmentioning
confidence: 99%